Mechanical performance of rubberized cement paste with calcium sulfoaluminate cement addition. (10th January 2021) - Damiani, Robbie M.; Mondal, Paramita; Lange, David A.
Highlights: The first study to use expansive cement to improve the interface of rubber and paste. CSAin rubberized cement at optimal dose increases compressive and pullout strength. CSA cement in rubberized cement at optimal dose increases damping ratio. SEM imaging shows lower rubber-paste interfacial gap is present when CSA is used. Abstract: Due to an increasing amount of waste tires produced yearly, environmental concerns arise as waste tires in landfills pose both a fire hazard, and a habitat for rodents and mosquitos. As a result, the reuse of waste tires in the form of waste rubber in concrete has been attempted. Previous research work has shown that the inclusion of waste rubber in concrete results in a drastic decrease in compressive strength. The limitations regarding the use of rubberized concrete are related to the interfacial transition zone between rubber and paste. Due to mismatch in free surface energy between rubber and cement paste, an interfacial gap is often reported to be present. This investigation aims to determine the effect of expansive cement, specifically calcium sulfoaluminate cement (CSA), has on the performance on rubberized cement samples, and its effect on the interfacial transition zone. A comprehensive experimental plan was carried out including pullout and compressive tests, scanning electron microscopy (SEM) imaging of fractured surface, and non-destructive tests through resonant frequency and dynamic mechanical analysis (DMA); furthermore, a temperature sweep via DMA was done to determine damping factor as a function of temperature. Results from compressive strength indicate a marked increase in the performance of rubberized samples with expansive cement. Pullout results, dynamic modulus and damping ratio values, shrinkage measurements, and scanning electron microscopy (SEM) imaging validate the hypothesis that a decreased interfacial gap at the rubber-paste interface obtained from using expansive cement results in increased mechanical performance.